Evolution Reactions: Monodisperse Ternary NiCoP Nanostructures as a Bifunctional Electrocatalyst for Both Hydrogen and Oxygen Evolution Reactions with Excellent Performance (Adv. Mater. Interfaces 4/2016). Issue 4 (22nd February 2016) - Wang, Chunde; Jiang, Jun; Ding, Tao; Chen, Guihuan; Xu, Wenjing; Yang, Qing
Abstract : In article number 1500454, Q. Yang and co‐workers produce monodisperse ternary NiCoP via a facile one‐pot hot‐solution method for the first time. The NiCoP nanoparticles exhibit excellent catalytic activity and durability for both hydrogen evolution reactions and oxygen evolution reactions. This work has the potential to promote intensive investigations of transition‐metal‐phosphide solid solutions for a wide variety of applications.